Correction: Non-spherical micro- and nanoparticles in nanomedicine. Issue 5 (5th March 2020) - Zhu, Xingjun; Vo, Chau; Taylor, Madelynn; Smith, Bryan Ronain
Abstract : Correction for 'Non-spherical micro- and nanoparticles in nanomedicine' by Xingjun Zhu et al., Mater. Horiz., 2019, 6, 1094–1121.